Empowering Women in the Face of Body Ideals: A Scoping Review of Health Promotion Programs. (June 2022) - Chinn, Victoria; Neely, Eva; Shultz, Sarah; Kruger, Rozanne; Hughes, Roger; Thunders, Michelle
Achieving women's health equity and empowerment is a global priority. In a Western context, women are often disempowered by the value society places on body size, shape or weight, which can create a barrier to health. Health promotion programs can exacerbate women's preoccupations with their bodies by focusing outcomes toward achieving an "ideal" body size. Women's health promotion activities should be empowering if the desired outcomes are to improve their health and well-being long-term. This review sought to identify key elements from health promotion programs that aimed to empower women. A search was conducted in PubMed, MEDLINE, Web of Science, Scopus, CINAHL complete, and Academic Search Premiere databases. The search yielded 27 articles that collectively reported on 10 different programs. Through thematic synthesis, each article was analyzed for (1) key program features employed to empower women and (2) how such programs evaluated women's health. Seven themes resulted, of which five describe key empowering features ( active participation, social support, sustainable change, holistic health perspective, strength-based approach ) and two evaluation characteristics ( assessment across multiple health domains and a mixed-method design ). The findings from this review can assist health promoters to design and improve initiatives that aim to empower women.